Barriers in international cooperation activities in science-technology field - Long, Dinh Thi Thanh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2019)
International cooperation activities in science-technology field play important roles in knowledge economy which involves many actors. From one side, international cooperation brings rich benefits for involved partners such as shortening gaps between nations, enhancing competitiveness of nations and others, and, from another side, posing many challenges. This paper focuses on barriers rising from cooperation process and international cooperation policies in science-technology field and, then, proposes initiatives to overpass barriers. Code: 19050601